Effect of in ovo injection with different levels of Canthaxanthenon on Some cellular and biochemical characteristics of the plasma chicks hatched - Mahmood Abdulateif, Khaldoon; Hashim Aued, Hassan (Journal of Kerbala for Agricultural Sciences, 2017)
This experiment was conclucted to evaluated the effect of Canthaxanthen injection eggs with different levels on hatchability and phenotypic trait of chicken. Seven hundred eggs hatching (Rose 308) were divided into five groups (140/ group). Treatment groups were injected at the fourteenth day of incubation in the amniotic fluid; the eggs were injected with (0.1) ml/egg from melting solution with different concentrations of the CX as follows: T1 negative control (without injection), T2- positive control (injected with sterile distilled water only), -T3, T4 and T5 injected by 0.5 , 1.0 , 1.5 mg CX/egg, and after hatching some of the cellular and biochemical characteristics of the hatching chicks and at 14 day old were studied .The data showed that CX injection led to significantly ( p<0.05) elevated in packed cell volume (PCV) , total red blood cell (RBC) ,total white cell (WBC) ,Hemoglobin concentration(Hb) and total protein . However, the result revealed that there was a significant decreased (P<0.05) in the concentration of Glucose , Triglycerides , cholesterol and Low density lipoprotein (LDL).